PERSUASIVE COMMUNICATION STRATEGY OF BANDAR LAMPUNG CITY ENVIRONMENTAL OFFICE IN WASTE MANAGEMENT - Ardiyanti, Ika; Choiriyati, Sri; Azizah, Meylin; Sasora, Fajar (Journal of Public Relations and Digital Communication (JPRDC), 2024)
ABSTRAC Waste generation continues to increase rapidly along with population growth and changes in people's diets and lifestyles, thus affecting the amount of waste produced, the type of waste and the characteristics of different waste. One of them to minimize the impact of increasingly accumulated waste can be done through inviting the community to participate in maintaining the cleanliness of the environment through persuasive communication strategies to the community. The purpose of this study was to find out the persuasive communication strategy of the Environmental Office in waste management, a study in Kampung Baru Tiga Kelurahan Panjang Utara. This research uses qualitative methods. Data were collected obtained from interviews, observations and field notes. The result of this study is that Waste Management has not been carried out properly due to low public awareness and concern about proper waste management. To increase public awareness and public concern for the environment and waste management, the Environmental Office and Village Apparatus have conducted education to the community in the form of socialization, counseling, and advertisements about waste management to be useful including compost and ecobricks. Handling waste problems needs to increase public awareness of the importance of environmental cleanliness by the Environmental Agency as the main agency responsible for waste management must establish good relations with the community so that the waste management program is in accordance with its goals.